The role of modern educational theories and computer technology in the development of intelligence - Ahmadov, Humeyir; Ismayilova, Bahar; Humbataliyev, Rovshan (International Journal of Psychosocial Rehabilitation, 2020)
We observe that the psychological state of each student is different in the learning process. Some students lack self-confidence, are ashamed that their answers are wrong during class and refuse to answer, thus becoming more passive. The pupil who solves problems interactively in front of a personal computer and plays educational computer games is no longer afraid of him or the machine, there is a return between him and the computer, he enters the answers that ’he thinks in the computer, sees his errors immediately tries to correct them. increases. From this point of view, the importance of educational computer games in the independent activity of each person cannot be compared to anything. Educational computer games have repeatedly proven to be a very effective tool for bringing learning to a new form in the classroom and in extracurricular activities. Those who play these games criticize the problems they face and find different ways to solve them. The player later acquires certain skills that will be useful to him and uses them to play more successfully, his skills constantly improve during the game. Type of Paper— Review